Supporting Emirati females leadership skills through teaching them how to debate - Badran, Dany (2016)
In response to the emerging need in the United Arab Emirates to empower young women and prepare them for future leadership tasks, a debate teaching intervention was organized in two phases at a public University in Dubai. During that intervention, 137 female Emirati students were taught the basics of debate and then participated in a debate session on a topic of general interest (Dubai EXPO 2020). Results show that participants observe a clear change in how they perceive themselves as leaders as a result of the intervention. Moreover, their leadership discourse as measured in terms of the persuasiveness of their expressed arguments at a group level was seen to improve more when the debate format followed had a formal structure than when it was flexible. Implications are discussed regarding the transformative learning function of debate as a training tool and its effect on leadership self-efficacy.